2020
DOI: 10.1038/s41423-020-00578-4
|View full text |Cite
|
Sign up to set email alerts
|

Themis regulates metabolic signaling and effector functions in CD4+ T cells by controlling NFAT nuclear translocation

Abstract: Themis is a T cell lineage-specific molecule that is involved in TCR signal transduction. The effects of germline Themis deletion on peripheral CD4+ T cell function have not been described before. In this study, we found that Themis-deficient CD4+ T cells had poor proliferative responses, reduced cytokine production in vitro and weaker inflammatory potential, as measured by their ability to cause colitis in vivo. Resting T cells are quiescent, whereas activated T cells have high metabolic demands. Fulfillment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“… 30 NFAT proteins also take part in metabolic signaling and effector functions. 29 NFAT5, a member of the Rel transcription factor family, is involved in the pathogenesis of diverse cancers. It was reported that NFAT5 acted as an oncogene in renal cancer, breast cancer, pancreatic cancer, and glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“… 30 NFAT proteins also take part in metabolic signaling and effector functions. 29 NFAT5, a member of the Rel transcription factor family, is involved in the pathogenesis of diverse cancers. It was reported that NFAT5 acted as an oncogene in renal cancer, breast cancer, pancreatic cancer, and glioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mTOR by rapamycin leads to cell cycle arrest and is a potent T cell immunosuppressant [46]. The T-cell-specific protein Themis, which is important in thymocyte positive selection, has recently been shown to affect the AKT pathway and its downstream effects in mature T cells [47], and also affects metabolism [48,49].…”
Section: Metabolic Reprogramming During T Cell Activationmentioning
confidence: 99%
“…Themis interacts with and regulates the phosphatases Shp1 ( Ptpn6 ) and Shp2 ( Ptpn11 ), although the precise mechanism is controversial ( 39 , 41 43 ). Themis deficiency affects the metabolic response of T cells to TCR stimulation ( 44 ). Post-selection deletion of Themis reduces the homeostatic response of peripheral CD8 + T cells to self-pMHC ( 45 ).…”
Section: Introductionmentioning
confidence: 99%